Tracing the roles of soft law in human rights - Lagoutte, Stéphanie; Gammeltoft-Hansen, Thomas; Cerone, John (Oxford : Oxford University Press, 2017)
Building on a thorough analysis of relevant case studies, this volume systematically explores the roles of soft law in both established and emerging human rights regimes.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 7, 2016).
Keywords: Human rights; Soft law; Law; International law